2019
DOI: 10.3390/cells8060577
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Gut Microbiota in P28GST-Mediated Anti-Inflammatory Effects: Experimental and Clinical Insights

Abstract: An original immuno-regulatory strategy against inflammatory bowel diseases based on the use of 28 kDa glutathione S-transferase (P28GST), a unique schistosome protein, was recently proposed. Improvement of intestinal inflammation occurs through restoration of the immunological balance between pro-inflammatory T-helper 1 (Th1) responses and both T-helper 2 (Th2) and regulatory responses. However, detailed mechanisms explaining how P28GST prevents colitis and promotes gut homeostasis remain unknown. Considering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
3
15
0
Order By: Relevance
“…In that study, too, after the P28GST treatment, the IgG levels increased; IgE levels increased only slightly, and IgA levels did not increase [7]. Finally, we detected no significant changes in gut microbiota composition, as reported previously [9].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In that study, too, after the P28GST treatment, the IgG levels increased; IgE levels increased only slightly, and IgA levels did not increase [7]. Finally, we detected no significant changes in gut microbiota composition, as reported previously [9].…”
Section: Discussionsupporting
confidence: 86%
“…The P28GST-driven reduction in colonic inflammation was associated with a reduction in the Th1/Th17 inflammatory response, and an increase in the immunoregulatory response involving Th2/Treg cells and M2 macrophages [5,8,9]. Specifically, P28GST combines the antigenic properties and regulatory enzymatic activities of the antioxidant GST with the anti-inflammatory properties of prostaglandin-D-synthase.…”
Section: Introductionmentioning
confidence: 99%
“…The rarefaction curves for bacterial species as a function of the number of sequences (representing the total bacteria diversity) were similar in the two data sets; whereas the curve's plateau showed that the sequencing was deep enough to cover all microbial representatives ( Figure 6A). The mean number of OTUs per individual (~250) was in line with other studies in mice 51,58 ( Figure 6B). The specific richness of the observed OTUs was similar before and after Zn supplementation.…”
Section: Impact Of Dietary Zn Supplementation On the Gut Microbiotasupporting
confidence: 90%
“…The DNA extraction, 16S metagenomic analysis, and bioinformatics analyses were performed according to optimized, standardized methodologies developed by GenoScreen (Lille, France), as described previously. 51 The DNA was extracted from 200 mg of mouse feces. The procedure was based on the use of the QIAamp stool DNA Kit (Qiagen, Courtaboeuf, France) but various preliminary mechanical and chemical lysis steps were added, in order to fully lyse bacteria in general and Gram-positive bacteria in particular.…”
Section: Microbiota Analysis In Feces From Znsupplemented Animalsmentioning
confidence: 99%
See 1 more Smart Citation